Work accidents and disability in municipal police of Iribarren of de Lara state (Revista Venezolana de Salud Pública, 2020)
The objective of this research was to determine the characteristics of work accidents and disability in the municipal police of Iribarren, Lara state. The study was framed in a descriptive, transversal field research. A target population of 297 workers of said security body was selected. A previously validated questionnaire was applied through the trial of three experts, using the interview technique, in order to determine the socio-demographic and work aspects of the police, the epidemiological and occupational characteristics of work accidents, clinical and work characteristics of work accidents and disability according to clinical-legal aspects. The most significant results were: 37.71% of the policemen were aged 33-37 years, 88.55% were male, their educational level was secondary at 50.84%, marital status is 54.88%, 84.85% had a mixed shift, the operational range was 94.61%, 41.08% of the police officers were officers added, in terms of seniority it is 6 to 10 years in 51.85%. The frequency of accident was 59.60%, of the instruments that caused the accidents were firearms, 57.85%, the activity carried out at the time of the accident was patrolling at 22.60%, the type of accident was for the fact at 51, 98%, 73.45% of the police officers did not notify the accident, the anatomical site most affected were the upper limbs 27.68%, the severity of the injury was severe in 42.37%, the most common type of disability was the partial permanent at 38.42%. This study is a contribution for the Municipal Police and for similar organizations, because their results provide statistical data that could be used to carry out preventive programs that allow finding solutions to the problem of work accidents and disability.
Keywords: Accident; disability; pólice,; work injuries